A Crucial Moment for Reflection on the Importance of Ethical Leadership in Academic Medicine. Issue 2 (February 2021) - Angelos, Peter; Devon, Karen; Ferreres, Alberto R.; McLeod, Robin; Ellison, Edwin Christopher
Abstract : N/A: The extreme disturbances caused by the COVID -19 pandemic on our academic medical centers compounded by a recurrent surge of violence against people of color have reopened our wounds exposing fragility, inequality, and continued racial disparities in society and health. At the center of this severe institutional disruption, leaders will be compelled to take action to keep their constituents and patients safe and their hospitals and departments afloat during and after a pandemic, all while simultaneously addressing and implementing the cultural changes required to eliminate systemic racism and discrimination. Organizational disruptions of this magnitude will naturally test one's principles, loyalties and responsibilities while challenging the practical burdens of leadership. If the goal of responding to these upheavals is to bring them to resolution and ultimately to bring about organizational change for the better, ethical leadership is critical. Applying ethical principles allows leaders to chart clear paths to solutions both in the short and long term. We review the principles of ethical leadership exemplified by a case illustration and provide a novel resource to help ensure ethical leadership in academic medicine and beyond.